Features changes of the optic nerve and conjunctiva after exposure to high-frequency electric welding of biological tissues when enucleation of the eyeball (experimental research) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Relevance of the work is conditioned by the need to reduce the num¬ber of complications after enucleation of the eyeball during the intra- and postop¬erative period.Purpose of the study. To determine the clinical and morphological peculiarities of tissue changes of the optic nerve and conjunctiva using electric current of high frequency — 66 kHz and enucleation of the eyeball in the experiment. Material and methods. Investigations were carried out in 12 rabbits, of which eight (the main group) underwent enucleation of the eyeball using HFEWand in 4 control animals enucleation was performed according to the standard procedures. Evaluated clinical signs were the following: swelling of the tissues of the orbit, the state of postoperative wound edge, presence of the discharge from the conjunctival cavity. There were made histomorphological studies of the conjunctiva and optic nerve after exposure to HFEW.Results. During surgery using HFEW, bleeding after transection of the muscles and neurovascular bundle was absent, reducing the time of surgery by an average of 10 minutes compared with the control group. Histological studies have shown that in using HFEW closing of the wound is the result of deposition of fibrin with subsequent epithelization of the surface and fibrotization of the subepithelial tissue, which contributes to an earlier reparative processes in the tissue.     Conclusions. The clinical and histological studies showed benefit of the enucle- ation technique using HFEW compared with the conventional method.
Keywords: COnjunctiVa; optic nerve; enucleation; highfreqUenCy electric welding of biologiCal tissues